2016
DOI: 10.1016/j.jsams.2015.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a model of motor competence in children and adolescents

Abstract: a b s t r a c tObjectives: This study was aimed at developing a quantitative model to evaluate motor competence (MC) in children and adolescents, to be applicable in research, education, and clinical contexts. Design: Cross-sectional. Methods: A total of 584 children (boys n = 300) with ages between 6 and 14 years were assessed using nine well known quantitative motor tasks, divided into three major components (stability, locomotor and manipulative). Structural equation modelling through EQS 6.1 was used to fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
89
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(99 citation statements)
references
References 21 publications
1
89
0
4
Order By: Relevance
“…To our knowledge, this is the first study to analyze the relationship between MC and a composite HRF index across a large sample of male and female children and adolescents, using a validated instrument [12] that includes the three theoretical components proposed by Gallahue and colleagues [10]. However, the current study presents some limitations.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…To our knowledge, this is the first study to analyze the relationship between MC and a composite HRF index across a large sample of male and female children and adolescents, using a validated instrument [12] that includes the three theoretical components proposed by Gallahue and colleagues [10]. However, the current study presents some limitations.…”
Section: Discussionmentioning
confidence: 90%
“…MC was evaluated with a valid quantitative instrument developed by Luz and colleagues [12]. This instrument is composed of two tests for each MC category (stability, locomotor, and manipulative).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…26 There is a wide range of movement battery tests that assess MC as a whole or as individual subsections such as manual dexterity, throwing and catching, and balance tasks (static and dynamic), with specific tests for different age groups. [29][30][31] Evidence has suggested that measures of overall MC are invalid due to vast differences in fine and gross MC in a single participant with many tasks not representing normal distributions. These subsections of MC should be assessed separately.…”
Section: Introductionmentioning
confidence: 99%